PENGARUH PENDIDIKAN KEWIRAUSAHAAN, EKSPEKTASI PENDAPATAN DAN SELF EFFICACY TERHADAP MINAT BERWIRAUSAHA (Studi Pada Mahasiswa Pendidikan Ekonomi Universitas Bhinneka PGRI Tulungagung) - Anna Mufidatul Afifah; Maria Agatha SWH (Jurnal Cita Ekonomika, 2022)
This study aims to determine the effect of entrepreneurship education, income expectations, and self-efficacy on interest in entrepreneurship by studying economic education students at the University of Bhinneka PGRI Tulungagung. Where this research was conducted with the type of quantitative research and hypothesis testing method using saturated sampling technique. Educational variables are measured from understanding to generate innovative ideas, increasing students' understanding of the attitude of an entrepreneur, activities that inspire students to become entrepreneurs, increasing student skills to develop business plans. Then income expectations are measured based on high income, unlimited income, the effect of the amount of income received, the effect of increasing and decreasing the income received. Furthermore, self-efficacy is measured by three indicators, namely magnitude, strength, and generality. As well as interest in entrepreneurship as measured by feelings of pleasure towards entrepreneurship, the desire to work independently, the desire to take on challenges, the desire to create something new. The sample used in this study was 54 respondents with data retrieval via google form. The results of the study show that entrepreneurship education, income expectations, and self-efficacy partially affect the interest in entrepreneurship.